2012
DOI: 10.1002/ange.201206533
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Based Redox Catalysis in the Direct Traceless Staudinger Ligation of Carboxylic Acids and Azides

Abstract: Redox‐Katalyse: Arylamide, Imide, Lactame und Dipeptide werden durch eine direkte Staudinger‐Ligation, die über eine Phosphin‐basierte Redoxkatalyse verläuft, hergestellt (siehe Schema). Mechanistische Studien deuten auf ein Phosphoniumcarboxylat‐Intermediat hin, das zu einer 1,3‐Acylmigration und somit zur Bildung der C‐N‐Bindung führt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Nowadays, a phosphine‐catalyzed Staudinger ligation involving the direct coupling of carboxylic acids and azides has been developed . The reaction was envisioned as a P(III)/P(V) redox‐driven cycle wherein an acid/base reaction of the carboxylic acid and aza‐ylide would form an activated phosphonium carboxylate in situ and thus enable catalytic C–N bond formation (Scheme ).…”
Section: Reactions With Electrophilesmentioning
confidence: 99%
“…Nowadays, a phosphine‐catalyzed Staudinger ligation involving the direct coupling of carboxylic acids and azides has been developed . The reaction was envisioned as a P(III)/P(V) redox‐driven cycle wherein an acid/base reaction of the carboxylic acid and aza‐ylide would form an activated phosphonium carboxylate in situ and thus enable catalytic C–N bond formation (Scheme ).…”
Section: Reactions With Electrophilesmentioning
confidence: 99%
“…[7] Subsequently others applied this reduction strategy to the Appel and Staudinger reactions. [8] In regard to the Wittig reaction, we found that a temperature of 100 8C was required to achieve a viable turnover rate of the phosphine oxide/phosphine required for adoption in a catalytic process. [9] Consequently, to decrease the reaction temperature an increase in the reactivity of either the phosphine oxide (toward reduction) or silane must be achieved.…”
mentioning
confidence: 99%
“…alkoxyphosphonium salts to achieve closure of a catalytic cycle. While this augurs badly for catalysis at first glance the pioneering demonstration of a catalytic aza-Wittig reaction by Marsden 26 along with the report of a catalytic Wittig reaction from O'Brien 27 demonstrated that catalysis of classical phosphorus-mediated reactions was achievable under synthetically useful conditions and a range of further impressive examples of phosphorous catalysis 28 have since appeared from Rutjes, 29 Ashfeld, 30 Woerpel 31 and Radosevich. 32…”
Section: Phosphorus-mediated Catalytic S N 2 Reactionsmentioning
confidence: 99%